1988
DOI: 10.1007/bf00174504
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous nicotine in Alzheimer's disease: a pilot study

Abstract: In the first study to examine direct nicotinic augmentation of central cholinergic functioning in Alzheimer's disease, six patients were studied in an intensive pilot study with three doses (0.125, 0.25, and 0.5 microgram/kg/min) of intravenous nicotine and placebo. Cognitive tests showed a decrease in intrusion errors on the middle (0.25 microgram) dose. Prominent behavioral effects were noted, with significant dose-related increases in anxiety and depressive affect. These results suggest that central nicotin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
130
1
3

Year Published

1991
1991
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 274 publications
(139 citation statements)
references
References 29 publications
(19 reference statements)
5
130
1
3
Order By: Relevance
“…In human studies, nicotine has been reported to improve information processing (12,13). Beneficial effects in patients with Alzheimer's disease have even been reported (14). In animal studies, faci litative effects on the delayed matching performance in monkeys has also been reported by other investigators (8).…”
Section: Discussionmentioning
confidence: 88%
“…In human studies, nicotine has been reported to improve information processing (12,13). Beneficial effects in patients with Alzheimer's disease have even been reported (14). In animal studies, faci litative effects on the delayed matching performance in monkeys has also been reported by other investigators (8).…”
Section: Discussionmentioning
confidence: 88%
“…In hu mans, nicotine is reported to increase arousal and at-tention as well as to decrease reaction time, prevent de cline in efficiency over time, and improve the ability to withhold inappropriate responses (Wesnes and War burton, 1983). In pilot studies (Newhouse et al 1988b(Newhouse et al , 1990, we have shown that intravenous nicotine pro duces small but measurable improvements in several cognitive tasks in AD patients. Recently, Jones and col leagues (1992) have shown that acutely administered nicotine can improve attention and speed of informa tion processing in AD patients.…”
mentioning
confidence: 74%
“…However, neither of these approaches is practicable for projected clinical use, whereas pharmacotherapy with nicotine is. Indeed, nicotine has been used to improve cognitive function in situations of cholinergic deficiency, such as in patients with neurodegenerative diseases (Newhouse et al, 1988), schizophrenia (Rezvani and Levin, 2004), or other situations exhibiting cognitive deficits (White and Levin, 1999). In animal models, nicotine improves hippocampal performance in aged rats with cognitive impairment or in young rats with cholinergic lesions (Levin, 1993).…”
Section: Discussionmentioning
confidence: 99%